Cauda Equina Cavernous Angioma - Adrian Jamesraj Jacob; Balamurugan Mangaleswaran; Sheba Jacob; Saranraj M.K (Indian Journal of Neurosurgery)
Cavernous angiomas are rare vascular lesions, most occurring supratentorially, with spinal cavernomas being even rarer. They have a varied magnetic resonance imaging (MRI) appearance which is usually not diagnostic. A 42-year-old man presented with progressive low backache for the past 5 years and was found to have a mild right ankle weakness. MRI showed an intradural extramedullary lesion at the L1 vertebral body level. Intraoperatively, a dark reddish-blue mulberry-like lesion was found attached to a nerve root that had to be sacrificed during the excision. Histopathology confirmed that it was a cavernous angioma and the patient had no added deficits postoperatively. Cauda equina cavernomas are extremely rare and hence not thought of as a differential preoperatively. They are relatively simple to remove but will mostly need the sacrifice of the adherent nerve root. Most cases do well postoperatively with stable deficits and some improving.